Gender-specific effects of meat consumption on type 2 diabetes: a narrative review of prospective cohort studies - Lombardo, Mauro (Frontiers in Nutrition, 2025)
Purpose of the reviewThis narrative review examines the association between meat consumption and the risk of type 2 diabetes mellitus (T2DM), with a focus on gender-specific effects.ResultsProspective cohort studies indicate that processed and red meat consumption is associated with an increased risk of T2DM, with stronger associations generally observed in men. In contrast, white meat shows weaker and inconsistent associations, with modest increases in risk reported more often in women.SummaryThe evidence supports the relevance of gender in dietary recommendations for the prevention of T2DM. Biological and behavioral differences, such as hormonal profiles, iron metabolism, fat distribution and culinary habits, may underlie sex-specific susceptibilities. Personalized dietary strategies should take these differences into account to improve prevention.